The Role of The Cangkuang Temple Site in Kampung Pulo as a Source of Entrepreneurial Activities - Alni Dahlena; Nana Supriatna; Acep Supriadi (Entrepreneurship Faculty, Universitas Garut, 2025)
The cangkuang temple site is a form of cultural heritage tourism whose existence should be preserved because it has essential value for history, knowledge, education, religion, and culture. This study aims to review the potential from the perspective of entrepreneurial sources. This study is a descriptive study with a qualitative approach. The population in this study were entrepreneurs around the cangkuang temple. Sampling by incidental sampling for visitors and people who do activities around the cangkuang temple, and purposive sampling for managers. Data collection techniques used are observation, interviews, questionnaires, and documentation. Data analysis techniques use data reduction, data presentation, and data verification. The results of this study can provide cangkuang temple shows that the richness of cultural values ​​​​owned by the site can be used as a source of inspiration in developing creative and educational products. Therefore, it can be concluded that the development of tourist destinations that can increase entrepreneurship in rural areas by using local cultural assets can encourage economic growth through job creation and increasing community income.